2004
DOI: 10.1097/01.ico.0000120783.31977.77
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Analysis of LASIK for the Correction of Refractive Errors After Penetrating Keratoplasty

Abstract: Purpose: To determine the long-term safety and effectiveness of laser-assisted in situ keratomileusis (LASIK) in the treatment of refractive errors following penetrating keratoplasty.Methods: A retrospective review was done of 57 eyes of 48 patients with anisometropia or high astigmatism who were unable to wear glasses or a contact lens after penetrating keratoplasty and who underwent LASIK for visual rehabilitation. Uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BCVA), and corneal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Visual acuity after enhancement was included in postoperative data. In most recent studies of one-step LASIK, enhancement was observed in 9% to 39% of cases [11,12,13]. In our study, the rate of enhancement was 8%.…”
Section: Discussionsupporting
confidence: 60%
“…Visual acuity after enhancement was included in postoperative data. In most recent studies of one-step LASIK, enhancement was observed in 9% to 39% of cases [11,12,13]. In our study, the rate of enhancement was 8%.…”
Section: Discussionsupporting
confidence: 60%
“…In some cases, anisometropia may develop, causing diplopia and blurred vision [5]. The management of these refractive problems is initially focused on conservative means – spectacle lenses and contact lenses – before introducing invasive procedures as surgical options [6].…”
Section: Discussionmentioning
confidence: 99%
“…Both microkeratome- and femtosecond laser-assisted LASIK have been shown to be effective in the correction of post-PK ametropia, particularly the spherical component [5]. Importantly, no significant changes to endothelial cell density could be demonstrated in post-PK patients who underwent microkeratome-LASIK [6]. …”
Section: Discussionmentioning
confidence: 99%